Indikasi Geografis Dalam Mendukung Pengembangan Kawasan Wisata Pertanian - Puti Mayang Seruni; Sridevi Ayunda; Budi Agus Riswandi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
Intellectual Property Rights in the form of geographical indications play a role in optimizing products with local regional wisdom, so that these products have economic value that can help the local communities. One of them is through Geographical Indication-based Agrotourism. However, the realization of a geographical indication application is complicated, takes a long time and is expensive. Good planning and management programs are also needed after obtaining geographical indications. This research aims to explore geographical indication policies in Indonesia, as well as elaborating on the potential of geographical indications as a key instrument in developing agricultural tourism areas. This research uses a normative approach with analytical descriptive. The data source used is secondary data consisting of primary legal materials in the form of Law Number 20 of 2016 concerning Trademarks and Geographical Indications and secondary legal materials. This research provides an overview of the history of geographical indication regulations in Indonesia. The geographical indication policy is expected to provide legal protection for products with reputation, quality and special characteristics due to geographical factors in the region of origin. To realize geographical indication-based agrotourism, awareness is needed from all parties, both the government and the community protecting geographical indications. Good governance and careful planning need to be prioritized. It is necessary to strengthen the environment, social and culture in society to build tourism-friendly areas. Hak Kekayaan Intelektual berupa indikasi geografis berperan dalam optimalisasi produk dengan kearifan lokal daerah sehingga memiliki nilai ekonomi yang dapat memajukan kesejahteraan masyarakat setempat. Salah satunya melalui Agrowisata berbasis Indikasi Geografis. Namun realiasasi permohonan indikasi geografis ini rumit, membutuhkan waktu lama, dan mahal. Perencanaan dan program pengelolaan yang baik juga diperlukan pasca perolehan indikasi geografis. Penelitian ini bertujuan untuk menggali terkait kebijakan indikasi geografis di Indonesia, serta mengelaborasi potensi indikasi geografis sebagai instrumen kunci dalam pengembangan kawasan wisata pertanian. Penelitian ini menggunakan pendekatan normatif yang bersifat deskriptif analitis. Sumber data yang digunakan adalah data sekunder yang terdiri dari bahan hukum primer berupa Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis dan bahan hukum sekunder. Penelitian ini memberikan gambaran mengenai historis pengaturan indikasi geografis di Indonesia. Kebijakan indikasi geografis diharapkan dapat memberikan pelindungan hukum terhadap produk dengan reputasi, kualitas dan karakteristik khusus karena faktor geografis daerah asal. Untuk mewujudkannya agrowisata berbasis indikasi geografis perlu kesadaran dari semua pihak baik pemerintah maupun masyarakat pelindung indikasi geografis. Tata kelola yang baik serta perencanaan dari hulu hingga hilir yang matang perlu di prioritaskan. Untuk membangun daerah ramah wisata maka penguatan lingkungan, sosial dan budaya dalam masyarakat menjadi komponen penting